Study of dynamics of accumulation of tanning substances in raw materials of plants of the genus Geum L. flora of Ukraine - S. А. Kozyra; О. В. Radko; О. S. Маlа; S. I. Stepanova; L. P. Міronets; О. М. Babenko (The State Expert Center of the Ministry of Health of Ukraine, 2022)
Recently, in the pharmaceutical market, much attention is paid to medicinal products obtained from medicinal plant raw materials. Of great current interest is a search for new plants with sufficient domestic raw material base in order to introduce them into medical practice as well as to develop herbal preparations. Promising sources of medicinal plant raw materials for the development of herbal preparations with antimicrobial, astringent, anti-inflammatory and hemostatic properties are species of Gravilate genus (Geum L.), which accumulate a wide range of biologically active substances, including polyphenols. Plants of Geum L. genus (Gravilate) belong to Rosoideae (Rosaceae family). Two species, Geum urbanum L. (Wood Avens) and G. montanum L. (Mountain Gravilate), grow in Ukraine, and are used in folk medicine as anti-inflammatory, astringent, hemostatic and wound healing agents. A significant amount of research articles devoted to the chemical composition and use of Geum L. species indicate the prospects for the study of domestic raw materials of Ukrainian flora. An aimof the present study was to quantify tannins and oxidizable phenolic compounds in the vegetative organs of G. urbanum L. and G. montanum L. The objects of the study were herb and rhizomes with roots of G. urbanum L. and G. montanum L. harvested in Sumskaya and Ivano-Frankivsk regions in April-September 2020-2021. The content of oxidizable phenolic compounds and tannins was determined by permanganometric titration and complexometric titration. The results obtained were in the range from 8.30% to 28.10%, and 2.66% to 14.35%, respectively. As a result, in herb and rhizomes with roots of G. urbanum L. and G. montanum L., oxidizable phenolic compounds and tannins were quantified using permanganometric titration and complexometric titration. Taking into account the high content of tannins in vegetative organs of the studied Geum species, these species can be classified as tannin-bearing plant materials. In G. urbanum L. herb, the maximum content of tannins was determined at flowering stage, while in rhizomes with roots - at the end of the vegetative stage (in autumn). Given the data obtained, the abovementioned vegetative stages are set as optimal for the procurement of G. urbanum L. plant materials.